Chemical Fractionation of Trace Elements in Arctic PM10 Samples - Conca, E; Malandrino, M; Giacomino, A; Inaudi, P; Giordano, A; Ardini, F; Traversi, R; Abollino, O (Atmosphere, 2021)
In this study, the information potential of a two-step sequential extraction procedure was evaluated. For this purpose, first of all the elemental composition of Arctic PM10 samples collected in Ny-angstrom lesund (Svalbard Islands) from 28 February 2015 to 21 October 2015 was investigated. Enrichment Factors, Principal Component Analysis and Hierarchical Cluster Analysis were performed to identify PM10 sources and to understand the effects of short- and long-range transport processes. The investigation of the potential source areas was also aided by taking into account back-trajectories. Then, the sequential extraction procedure was applied to some of the samples in order to obtain more information on these sources. This approach allowed us to establish that most of the elements prevalently having an anthropogenic origin not only were present in higher concentrations, but they were also more easily extractable in late winter and early spring. This confirms the common statement that the anthropogenic portion of the elements present in a sample is generally loosely bound to the particulate matter structure, and so it is more easily extractable and releasable on the Arctic snowpack. Moreover, in the samples collected in late winter and early spring, even the elements prevalently having a crustal origin were more easily extractable, probably due to the particle size selection occurred during the long-range transport.